2014
DOI: 10.1002/chem.201303923
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature ortho‐Alkoxylation and ‐Halogenation of N‐Tosylbenzamides by Using Palladium(II)‐Catalyzed CH Activation

Abstract: The N-tosylcarboxamide group can direct the room-temperature palladium-catalyzed C-H alkoxylation and halogenation of substituted arenes in a simple and mild procedure. The room-temperature stoichiometric cyclopalladation of N-tosylbenzamide was first studied, and the ability of the palladacycle to react with oxidants to form C-X and C-O bonds under mild conditions was demonstrated. The reaction conditions were then adapted to promote room-temperature ortho-alkoxylations and ortho-halogenations of N-tosylbenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 61 publications
2
20
0
2
Order By: Relevance
“…Unlike N ‐methoxybenzamide, N ‐(2‐benzoylphenyl)benzamides and N ‐tosylbenzamides underwent DAA efficiently with use of the Pd(OAc) 2 /PhI(OAc) 2 system. Thus, methoxylation of N ‐(2‐benzoylphenyl)benzamides occurred selectively at the benzamide unit at 100 °C [Equation ], whereas N ‐tosylbenzamides reacted even at room temperature, in some cases affording dimethoxylated products [Equation ] . These conditions were compatible with various substituents on the ring and the use of secondary alcohols.…”
Section: Amide Coordinating Groups and Related Tethersmentioning
confidence: 99%
“…Unlike N ‐methoxybenzamide, N ‐(2‐benzoylphenyl)benzamides and N ‐tosylbenzamides underwent DAA efficiently with use of the Pd(OAc) 2 /PhI(OAc) 2 system. Thus, methoxylation of N ‐(2‐benzoylphenyl)benzamides occurred selectively at the benzamide unit at 100 °C [Equation ], whereas N ‐tosylbenzamides reacted even at room temperature, in some cases affording dimethoxylated products [Equation ] . These conditions were compatible with various substituents on the ring and the use of secondary alcohols.…”
Section: Amide Coordinating Groups and Related Tethersmentioning
confidence: 99%
“…Initially the reaction was investigated with different oxidants including Na 2 S 2 O 8 , K 2 S 2 O 8 , oxone, O 2 , Ag salts and Cu(OAc) 2 and it was found that K 2 S 2 O 8 gave relatively superior yield of 4aa (compare entry 3 with entries 2, [4][5][6][7][8][9]. Next we examined the reaction in the presence of 0.5 equiv of additives including AcOH, MeSO 3 H and TFA and discovered that in each case the yield of 4aa was improved but the best yield was obtained with TFA (compare entries [13][14][15]. Next we examined the reaction in the presence of 0.5 equiv of additives including AcOH, MeSO 3 H and TFA and discovered that in each case the yield of 4aa was improved but the best yield was obtained with TFA (compare entries [13][14][15].…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the transition-metal catalyzed functionalization of ubiquitous but inert C-H bonds into C-C or C-X (X = halogen, O, N, S) bonds are of significant importance. 3 18 Ka mal (2014 ) 17 Kuang (201 4) 16 Wang (2010) 8 S ong ( 2014) 15 S un (2 014) 13 Urr iolabeitia (2015) 19 S un (2 013) 12 Wan g (2012) 9 S un (2012 ) seminal contributions of Sanford,[6][7] who demonstrated that the dehydrogenative coupling of aryl ring with alcohol under oxidative conditions, promoted by palladium in high oxidation states, affords alkoxylated aryl derivatives, there has been notable progress in the area [8][9][10][11][12][13][14][15][16][17][18][19][20] which is summarized in Fig. Among them, the directing group C-H activation is considered to be one of the most versatile strategies to achieve C-C and C-X couplings with good yields and selectivity, especially for C(sp2)-H bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The functionalizations including arylation, alkoxylation, acylation, olefination, amidation, nitration and halogenation have been achieved [15] . So far, the halogenation of aromatics catalyzed by Pd [15][16][17][18][19][20][21] , Rh [22,23] , Au [7] and Cu [24][25][26][27][28][29][30][31][32] has been developed. In the past decade, C-H activation/C-X(X=halogen) coupling catalyzed by precious metal has made great progress.…”
mentioning
confidence: 99%